Advocacy in Non-Adversarial Family Law: A Recommendation for Revision to the Model Code - Sowter, Deanne M (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
Family law is evolving towards non-adversarial dispute resolution processes. As a result, some family lawyers are representing clients who are trying to reach settlements that recognize their interests, instead of just pursuing their legal rights. By responding to the full spectrum of client needs, lawyers are required to behave differently than they do when they are representing a client in a traditional civil litigation file. They consider the emotional and financial consequences of relationship breakdown – things that are not typically within the purview of the family law lawyer. They objectively reality check with their clients, and they approach interest-based negotiations in a client-centric way. These lawyers view their role as that of a non-adversarial advocate, and their clients as whole people with interests that are not just legal. This paper draws on an empirical study involving focus groups with family law lawyers, to argue that the Federation of Law Societies of Canada’sModel Code of Professional Conductneeds to be updated to incorporate non-adversarial advocacy. The lawyers in the study viewed non-adversarial advocacy as being responsive to client needs, and in the interest of clients’ children. This paper draws from the study to establish what constitutes non-adversarial advocacy and then it presents a proposal for revising Rule 5 (Advocacy) of the Model Code.